Anti-infection effects of heparin on SARS-CoV-2 in a diabetic mouse model - Zhang, Zhongyun; Zhang, Ning; Lu, Xuancheng; Zhou, Min; Yan, Xiaoxiang; Gu, Weiqiong; Yang, Jingru; Zhang, Qin; Zhang, Cheng; Gong, Yuhuan; Jia, Mingjun; Zhang, Xiaoyu; et al. (Zoological research, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can result in more severe syndromes and poorer outcomes in patients with diabetes and obesity. However, the precise mechanisms responsible for the combined impact of corona virus disease 2019 (COVID-19) and diabetes have not yet been elucidated, and effective treatment options for SARS-CoV-2-infected diabetic patients remain limited. To investigate the disease pathogenesis, K18-hACE2 transgenic (hACE2 ) mice with a leptin receptor deficiency (hACE2-Lepr ) or high-fat diet (hACE2-HFD) background were generated. The two mouse models were intranasally infected with a 5×10 median tissue culture infectious dose (TCID ) of SARS-CoV-2, with serum and lung tissue samples collected at 3 days post-infection. The hACE2-Lepr mice were then administered a combination of low-molecular-weight heparin (LMWH) (1 mg/kg or 5 mg/kg) and insulin via subcutaneous injection prior to intranasal infection with 1×10 TCID of SARS-CoV-2. Daily drug administration continued until the euthanasia of the mice. Analyses of viral RNA loads, histopathological changes in lung tissue, and inflammation factors were conducted. Results demonstrated similar SARS-CoV-2 susceptibility in hACE2 mice under both lean (chow diet) and obese (HFD) conditions. However, compared to the hACE2-Lepr mice, hACE2-Lepr mice exhibited more severe lung injury, enhanced expression of inflammatory cytokines and hypoxia-inducible factor-1α, and increased apoptosis. Moreover, combined LMWH and insulin treatment effectively reduced disease progression and severity, attenuated lung pathological changes, and mitigated inflammatory responses. In conclusion, pre-existing diabetes can lead to more severe lung damage upon SARS-CoV-2 infection, and LMWH may be a valuable therapeutic approach for managing COVID-19 patients with diabetes.